Pengaruh Budaya Organisasi dan Lingkungan Kerja terhadap Kinerja Karyawan dengan Motivasi Kerja sebagai Variabel Intervening pada PT. Semen Padang - Asya Mulasari; Dori Mittra Candana; Selvi Zola Fenia (JURNAL RISET MANAJEMEN (JURMA), 2025)
This study aims to examine the Influence of Organizational Culture and Work Environment on Employee Performance with Work Motivation as an Intervening Variable using primary data obtained by distributing questionnaires to 75 employees as respondents, namely at PT. Semen Padang. In this study, the Structural Equation Modeling (SEM) analysis tool was used using Partial Least Square (PLS). The results of the study showed that (1) There is a significant positive influence of Organizational Culture on Work Motivation at PT. Semen Padang. (2) There is a significant positive influence of Work Environment on Work Motivation at PT. Semen Padang. (3) There is a significant positive influence of Organizational Culture on Employee Performance at PT. Semen Padang. (4) There is a significant positive influence of Work Environment on Employee Performance at PT. Semen Padang. (5) There is a significant positive influence of Work Motivation on Employee Performance at PT. Semen Padang. (6) There is a significant positive influence of Organizational Culture on Employee Performance through Work Motivation at PT. Semen Padang. (7) There is an insignificant positive influence of the Work Environment on Employee Performance through Work Motivation at PT. Semen Padang.